2000
DOI: 10.1177/0092070300283004
|View full text |Cite
|
Sign up to set email alerts
|

Representing the Perceived Ethical Work Climate among Marketing Employees

Abstract: This research develops and tests a measurement model representing the ethical work climate of marketing employees involved in sales and/or service-providing positions. A series of studies are used to identify potential items and validate four ethical-climate dimensions. The four dimensions represent trust/responsibility, the perceived ethicalness of peers’ behavior, the perceived consequences of violating ethical norms, and the nature of selling practices as communicated by the firm. Both first- and second-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
178
0
19

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(203 citation statements)
references
References 39 publications
6
178
0
19
Order By: Relevance
“…These findings are consistent with those of previous researchers who found that the correlation between EC and OC was positive and significant (Hunt et al, 1989;Kelley & Dorsch, 1991;Verbeke et al, 1996;Trevino et al, 1998;Singhapakdi et al, 1999;Babin et al, 2000;Schwepker, 2001;Oz, 2001;Valentine et al, 2002;Cullen et al, 2003;Vitell & Hidalgo, 2006;Tsui & Huang, 2008;Shafer, 2009;Zehir et al, 2011;Purhanudin et al, 2012).…”
supporting
confidence: 92%
“…These findings are consistent with those of previous researchers who found that the correlation between EC and OC was positive and significant (Hunt et al, 1989;Kelley & Dorsch, 1991;Verbeke et al, 1996;Trevino et al, 1998;Singhapakdi et al, 1999;Babin et al, 2000;Schwepker, 2001;Oz, 2001;Valentine et al, 2002;Cullen et al, 2003;Vitell & Hidalgo, 2006;Tsui & Huang, 2008;Shafer, 2009;Zehir et al, 2011;Purhanudin et al, 2012).…”
supporting
confidence: 92%
“…hierarchy vs. autonomy) which are associated with the concept of organisational climate like, for example, leadership style, interactional and communicational practices, role attributes, conflict management styles, systems of gratuity, form the organisational context, in which the members of the organisation act, communicate, and collaborate. Organisational climate criteria can affect socialisation processes that find their outcome in changes of individuals´ attitudes and behaviours (Babin/Boles/Robin 2000) also deal with ethical or moral constructs but they put emphasis on other components than the sociomoral atmosphere does. For example, the Ethical Climate Questionnaire identifies nine types of climate, but these nine types meet not the requirements of our operationalisation of the sociomoral atmosphere corresponding to the Kohlberg-and Lempert-groups.…”
Section: Theoretical Framework 21 the Sociomoral Atmosphere In Organmentioning
confidence: 99%
“…These include linking ethical climate with ethical behavior and success (Deshpande, 1996a); ethical climate types and facets of job satisfaction (Deshpande, 1996b); ethical climate and conflict with stress in the sales force (Schwepker, Ferrell, & Ingram, 1997); ethical climate and sales managers' intentions to reward or punish sales force behaviors (DeConinck & Lewis, 1997); ethical climate and person-organization fit (Sims & Keon, 1997); ethical climate and moral reasoning (Brower & Shrader, 2000); and ethical climates and the ethical dimension of decision making (Fritzsche, 2000). In addition, other researchers have attempted to develop different constructs describing ethical climate/culture (Treviño, 1990;Cohen, 1995;Treviño, Butterfield, & McCabe, 1998;Babin, Boles, & Robin, 2000). Primarily because of methodological deficiencies, the studies employing the EWC construct provide only limited empirical support for the theoretical construct, but they and the other proposed constructs do indicate the widening interest in and acceptance of ethical climates.…”
Section: Independence Rulesmentioning
confidence: 99%